Language Solving Creativity Efforts through The Brilliant Teaching Method At Smartgama Learning Guidance Institution - Budiyono, Sri (Journal of Education Research, 2023)
The purpose of this research is to find a solution on how to make teaching enjoyable and acceptable read: it can be understood by students. There are quite a number of learning methods that are used as learning philosophies from several tutors in the city of Surakarta. From these references, the writer takes one of the learning methods used at the Smartgama Tutoring Institute, known as the Brilliant Solution Method. This research is a case study research. The method used in this study is a qualitative research method. Sources of data used in the study are: cooperative learning activities, informants from teachers and students, document sources, and archives. The data analysis technique uses descriptive qualitative analysis. The components of the analysis include: data reduction, data presentation, and drawing conclusions atau data verification. The conclusions obtained are: the learning method used by the students at the Smartgama Learning Guidance Institute is a brilliant solution method, namely solving problems in an intelligent way, each of which has an abbreviation and philosophy as follows: B means brave, R means rational or reasonable, I means intellectual or learned, L means leader, leader or chairma n, head, principle, L means liberal willing to respect or accept different behavior or opinions from one's own; open to new ideas, I means interesting. A means applicable, N means notable,easy to remember, and T means Trick or tactic or strategy. The results of the trials carried out showed that with the brilliant solution method students could learn more happily, quickly in answering questions, calm, brave, and of course their academic scores increased.